Women’s perceptions of discrimination at work: Gender stereotypes and overtime—An exploratory study in Portugal - Rebelo, G.; Delaunay, C.; Martins, A.; Diamantino, M. F.; Almeida, A. R. (Administrative Sciences, 2024)
The aim of this study is to identify women’s perceptions of the main reasons for discrimination at work. Furthermore, the aim is to analyse the effects of public working time policies on gender equality and their impact on discrimination at work and on women’s career paths. This article presents a framework for the topic through an analysis of documents and literature, as well as an exploratory study carried out in Portugal. Working time policies since 2011 in Portugal are examined and through an empirical study, the impact of overtime on women’s work and careers is analysed. The documentary analysis carried out in Portugal shows the difficulties women face in reconciling work with family and personal life. While most studies focus on job satisfaction and women’s willingness to work long hours for better career progression, this paper examines gender discrimination at work associated with working time policies. Gender equality and women’s empowerment are among the goals set by the 2030 Agenda for Sustainable Development. This study, based on a survey completed by female employees, concludes that women feel discriminated against in their careers due not only to the persistence of gender stereotypes but also to long working hours. Studying women’s perceptions of the reasons for discrimination at work, as well as the relationship between working time and equality at work, can be important for understanding the under-representation of women in leadership positions and can help enrich public policies in this area.